Ресурсозберігаючі технології виробництва органічної продукції запорука розвитку екологічного туризму в регіоні - Безугла, Людмила Сергіївна; Bezuhla, Liudmyla (My University, 2019)
У статті проаналізовано сутність та особливості застосування ресурсозбері-гаючих технологій виробництва і переробки органічної продукції. Досліджено різноманітні погляди науковців стосовно трактування сутності поняття "екологічний туризм ". Визначено, що екологічний туризм — це зосереджений на природу вид туризму, котрий безпосередньо відбувається в природному середовищі і має певну сукупність ознак, які характерні лише цьому специфічному виду діяльності і обов'язково регламентуються нормами міжнародних стандартів. Невід'ємними особливостями екологічного туризму, на нашу думку, завжди є освітня природоохоронна та соціальна складова. Встановлено, що важливу роль також відіграє ставлення екотуристів до природи. Міжнародним товариством екологічного туризму розроблено та запропоновано сукупність принципів, яких обов'язково повинні дотримуватись екологічні туристи. Доведено, що в умовах стрімкого розвитку та популярності екологічного туризму, значної популярності також набуває виробництво органічної продукції, в першу чергу саме ресурсозберігаючі технології виробництва та переробки органічної продукції. The article analyzes the essence and peculiarities of using resource-saving technologies for the production and processing of organic products. Different views of scientists on the interpretation of the essence of the concept of "ecological tourism" are researched. It has been established that ecotourism is a naturally-oriented type of tourism that takes place directly in the natural environment and has a certain set of features specific to a specific activity and is necessarily regulated by international standards. In our opinion, the peculiarities of ecological tourism are always educational-ecological and social components. It is established that an important role is played by the attitude of ecotourists to nature. The International Society for Ecotourism (International Society of Ecotourism) has developed and proposed a set of principles that environmental tourists should adhere to. It is proved that in the conditions of rapid development and popularity of ecological tourism, production of organic products, in particular, resource-saving technologies of production and processing of organic products, is gaining in popularity. In the conditions of organic production, the organic system of agricultural production, as well as agricultural products, is closely linked to the relevant standards, which makes it possible to mark the products that define it as organic. An important attribute of organic production is certification, which covers all processes of production, namely processing, packaging and storage of organic products. Organic products are gaining popularity both for European and national consumption. Realizing that Ukraine has an extremely powerful agricultural potential, it can undoubtedly become one of the main exporters of organic products in the EU market. To achieve this goal, the key step is to switch to resource-saving technologies for the production and processing of organic products, which in turn will attract interested ecologic tourism. In modern realities, ecological tourism within the rural areas is not developed sufficiently.
Resource-saving technologies of production of organic production of the development of environmental tourism in the region
Keywords: виробництво; production; органічна продукція; organic products; ресурсозбереження; resource conservation; підприємство; enterprise; сертифікація; certification; стандарт; standard; екологічний туризм; ecological tourism